A comparison of a milieu-based Behavioural Activation Communication with treatment as usual for acute psychiatric inpatients. (27th November 2013) - Gollan, Jackie K.; Hoxha, Denada; Hanson, Bjorn; Perkins, Evelyn; Slade, Maureen; Roberts, Patricia
Abstract Aim Patient emotion, behaviour, and symptoms may explain avoidance of the daily programming on an acute psychiatric inpatient treatment milieu. We compared changes of emotion, behaviour, and symptoms among acutely ill psychiatric inpatients assigned to Behavioural Activation Communication (BAC), a newly designed milieu program, and those assigned to a unit representing treatment as usual (TAU). Method Participants included 144 adult inpatients treated between January 2011 and July 2011 at two similar psychiatric units at a medical centre. Psychiatric patients were assigned to either the BAC or the TAU unit based bed availability. At admission and discharge, patients completed the Brief Symptom Inventory, Positive Affect and Negative Affect Scale, and the Checklist of Unit Behaviors. Results A comparison of BAC and TAU patients showed greater relative change on positive affect and of behavioural activation with the daily programming. Conclusion The BAC program is associated with a significant increase of positive emotion and activation of inpatients.